ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2012-2014 - Rizki Amalia (AKT 16 UMY 207, 2016)
The aim of this research is to study the effect of profitability, company size, media exposure, leverage, and the board of commissioner size to the extensive disclosure of Corporate Social Responsibility (CSR). The data collecting technique in this research was done by tracing the company annual report in the corner of Indonesia Stock Exchange (IDX) of Universitas Muhammadiyah Yogyakarta. The populations of this research are all the manufacture companies listed in Indonesia Stock Exchange in 2012-2014 and there are 150 companies. The sample taking method is by purposive sampling so that it is obtained 112 research samples. The statistic method used in this research is multiple linear regression. According to the analysis, it is obtained that the leverage variable has positive effect to the extensive disclosure of CSR, the company size variable has negative effect to the extensive disclosure of CSR, while profitability, media exposure, and the board of commissioner size variables do not affect the extensive disclosure of CSR. Key Words: Profitability, Company Size, Media Exposure, Leverage, Board of Commisioner, and Disclosure of Corporate Social Responsibility